2016
DOI: 10.1021/acs.inorgchem.6b00525
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the Dimethylamino Functionality on a Multifunctional Framework for Regulating Metals, Amyloid-β, and Oxidative Stress in Alzheimer’s Disease

Abstract: The complex and multifaceted pathology of Alzheimer's disease (AD) continues to present a formidable challenge to the establishment of long-term treatment strategies. Multifunctional compounds able to modulate the reactivities of various pathological features, such as amyloid-β (Aβ) aggregation, metal ion dyshomeostasis, and oxidative stress, have emerged as a useful tactic. Recently, an incorporation approach to the rational design of multipurpose small molecules has been validated through the production of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…The scavenging ability of the different compounds against free radicals was measured by the Trolox (vitamin E analogue) equivalent antioxidant capacity (TEAC) assay, which can evaluate compounds’ capability of quenching ABTS cation radicals [ABTS .+ ; ABTS = 2,2′‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonic acid)] in both an organic solution (i.e., EtOH) and a biologically relevant environment (i.e., cell lysates) . As shown in Figure b, the TEAC values of L2‐b1 and L2‐b2 were determined (0.8 ± 0.1 and 1.9 ± 0.1 in EtOH; 0.7 ± 0.1 and 1.1 ± 0.1 in M17 lysates, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…The scavenging ability of the different compounds against free radicals was measured by the Trolox (vitamin E analogue) equivalent antioxidant capacity (TEAC) assay, which can evaluate compounds’ capability of quenching ABTS cation radicals [ABTS .+ ; ABTS = 2,2′‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonic acid)] in both an organic solution (i.e., EtOH) and a biologically relevant environment (i.e., cell lysates) . As shown in Figure b, the TEAC values of L2‐b1 and L2‐b2 were determined (0.8 ± 0.1 and 1.9 ± 0.1 in EtOH; 0.7 ± 0.1 and 1.1 ± 0.1 in M17 lysates, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…The fluorescence imaging probes detected the presence of soluble Aβ form in in vivo experiment ( Zhang et al, 2013 ). Antiamyloidogenic property of aminoquinoline derivatives in both the absence and presence of metal ions was investigated, revealed that dimethyl amino group is the structural element essential for giving antiamyloidogenic activity ( Derrick et al, 2016 ). Ferulic acid is a small phenolic molecule possessing strong antioxidant properties and inhibiting Aβ aggregation ( Bramanti et al, 2013 ).…”
Section: Chelation With β-Amyloid Aggregation Inhibitionmentioning
confidence: 99%
“…Quinolone inspired molecules with a metal-binding component and antioxidant activity were designed by many research groups. Compounds exhibited antioxidant potential through binding metal ions, quenching radical ions via phenolic group thus preventing redox cycling ( Braymer et al, 2011 ; Savelieff et al, 2014 ; Derrick et al, 2016 ). The prevention of generation of free radicals is important since it leads to oxidative damage which ultimately causes neuronal cells death.…”
Section: Chelation With Antioxidant Propertymentioning
confidence: 99%
“…All of the PET imaging probes in clinical trials contain a monomethylamino or dimethylamino group that confers binding specificity to Aβ aggregates . Moreover, a recent study has reported that the blood‐brain barrier (BBB)‐permeable chemical reagent, N,N‐dimethyl‐p‐phenylenediamine (DMPD) can interact with both metal‐free Aβ and metal−Aβ and alter their aggregation pathways . Also, some authors have reported that chemical structural moieties such as the dimethylamino functionality are essential to tune the reactivity of small bifunctional molecules toward metal‐induced Aβ aggregation and neurotoxicity …”
Section: Introductionmentioning
confidence: 99%